Pneumatic dilation improves esophageal emptying and symptoms in patients with idiopathic esophago‐gastric junction outflow obstruction. Issue 3 (10th December 2018) - Clayton, Steven B.; Shin, Claire M.; Ewing, Alex; Blonski, Wojciech; Richter, Joel
Abstract: Background and aims: Idiopathic Esophago‐gastric outflow obstruction (EGJOO) is a new clinical entity resulting in delayed esophageal emptying secondary to a poorly relaxing lower esophageal sphincter. Little is known about treatment outcomes of idiopathic EGJOO patients. The aim of this study was to investigate the clinical response of pneumatic dilation (PD) in idiopathic EGJOO patients with a standing barium column and/or with pill arrest on timed barium esophagram (TBE) before and after undergoing PD. Methods: Idiopathic EGJOO patients with retained liquid barium on TBE at 1 minute and/or with pill arrest in esophagus at 5 minutes were included. Patients were treated with PD and evaluated with post‐procedural TBE. Results: A total of 33 patients with Idiopathic EGJOO and poor esophageal emptying on TBE were treated with PD. 67% of Idiopathic EGJOO patients reported subjective symptom relief, 18% improved and symptoms later recurred, 6% were lost to follow up, and 9% reported no change. TBE results of pre‐PD showed 1 minute average barium column height of 11.0 cm and 1 minute barium column width of 1.7 cm. There was significant decrease in 1 minute liquid barium column height and width ( P < 0.001 and <0.001, respectively) as well as significant improvement in pill passing ( P < 0.006) after undergoing PD. No complications occurred after PD. Conclusion: PD is an effective initial treatment for Idiopathic EGJOO patients with abnormal TBE. Pneumatic dilation relieved symptoms and improved esophageal emptying in Idiopathic EGJOO patients on TBE Abstract : Esophagogastric‐junction outflow obstruction (EGJOO) is characterized by elevated lower esophageal sphincter relaxation pressure (IRP > 15 mmHg) in combination with intact peristalsis. In 33 patients with EGJOO and abnormal esophageal emptying on TBE, PD relieved dysphagia symptoms and improved esophageal emptying in EGJOO patients on TBE without complication.